A DEVELOPMENT STRATEGY OF DISTRICT HEARTH SYSTEM, TAK PROVINCE - Lertkhampom, Pramot (Journal of Buddhist Anthropology, 2022)
The objectives of this research were to: 1) study problems condition and factors related to operations of district health network at Tak province, and 2) determine and assess strategies for developing district health networks at Tak province. By using mixed-methods research was research and development model (R&D) such as: 1) study the problems condition and operational factors by using questionnaires and group discussions, the sample group was (1) district level such as hospital director, public health and person in charge, and (2) sub-district level such as director of hospital health promotion, board, officer and sub-district administrative organization for totally 370 persons, 2) study strategies by using an in-depth interview form that the informant was 1) director of the hospital 2) district public health system 3) district health system of the hospital 4) district health system of district public health 5) president or permanent secretary of the sub-district administrative organization and 6) committee of 12 persons, 3) strategic formulation by using in-depth interview of health professionals of 10 persons, and 4) to evaluated strategies by using satisfaction survey, the sample group was Yokkrabat sub-district, Sam Ngao District totally 75 people. All selecting a specific sample. Data were analyzed by statistical frequency, percentage, mean, standard deviation and content analysis. It was found that: 1) the operating condition was: 1.1) collaborate, 1.2) leadership, 1.3) member participation, 1.4) work efficiency, 1.5) resource management, 1.6) health service, and 1.7) community engagement. The overall problem was moderate ( = 2.86) on the highest mean such as: organization chart and administration ( = 3.55) that it followed by sharing and developing human resource ( = 2.73), and next the factors such as: internal factor was policy ( = 3.32), and external was Technology ( = 3.23). 2) The strategic formulation such as vision, mission, goals and strategy that were: 2.1) developed a holistic health management, 2.2) promoted health care innovations through models, and 2.3) developed the potential of competent network personnel, manage all dimensions of health, assessment results were appropriate, possible, value = 4.53, average >3.51 or more that shown pass the criteria.